Low Cost Removal Of Disperse Dyes From Aqueous Solution Using Palm Ash. - Isa, M Hasnain; Lee, siew Lang; A H, Faridah; A Aziz, Hamidi; Ramli, N Azam; Dhas, Jaya Paul A (Universiti Sains Malaysia, 2005)

(untitled)
Palm oil and textile industries are important contributors to Malaysia's economic growth. However, these industries also generate various pollutants of the environment. This research explores the possibility using a low cost adsorbent i.e. ash produced from palm oil factory, for the removal of dyes from aqueous solution.